2017
DOI: 10.1515/med-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring health inequalities at the municipal level: Lithuanian experience

Abstract: AbstractThis study aimed to assess the attitudes of Lithuanian public health professionals towards health inequality monitoring in municipalities.The survey was conducted in public health bureaus (PHBs) and administrations of municipalities in March 2015. All employees of PHBs, all municipal doctors and all employees of health departments were invited to participate in the study (N=318; response rate, 47.2%).The study participants had positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Study results have revealed that the most common obstacles and pitfalls for tackling health inequalities are as follows: lack of credibility of statistical data, lack of uniform attitude towards health inequalities, lack of leadership and weak intersectoral collaboration. A more detailed description of this study and results are presented elsewhere [7][8][9][10][11][12][13][14]. These outcomes implicitly supported the directions for further actions in planning and running the project -development of monitoring system, preparations of recommendations for reduction and capacity building for public health professionals.…”
Section: Main Textmentioning
confidence: 56%
“…Study results have revealed that the most common obstacles and pitfalls for tackling health inequalities are as follows: lack of credibility of statistical data, lack of uniform attitude towards health inequalities, lack of leadership and weak intersectoral collaboration. A more detailed description of this study and results are presented elsewhere [7][8][9][10][11][12][13][14]. These outcomes implicitly supported the directions for further actions in planning and running the project -development of monitoring system, preparations of recommendations for reduction and capacity building for public health professionals.…”
Section: Main Textmentioning
confidence: 56%
“…Šiame projekte grupės diskusijomis buvo siekiama atskleisti sritis/klausimus, kurie vėliau buvo taikomi kiekybinio tyrimo klausimynui parengti. Kiekybinio tyrimo metu gauti rezultatai yra aptarti kitose publikacijose [7,8].…”
Section: įVadasunclassified
“…It covered institutions that are related to tackling health inequalities at national and local levels. Study results have revealed that common obstacles and pitfalls for addressing health inequalities are related to: the lack of credibility of statistical data; a lack of uniform attitude toward health inequalities; the absence of practical guidelines; and a lack of inter-institutional collaboration [ 9 , 10 ]. These results suggested directions for further actions in conducting the project, such as the development of monitoring systems, and the preparation of recommendations for reduction and capacity building for public health professionals.…”
Section: Introductionmentioning
confidence: 99%